Non Performing Loan, Loan to Deposit Ratio, Good Corporate Governance, Net Interest Margin, Return on Assets, Capital Adequacy Ratio dan Economic Value Added Terhadap Harga Saham - Supriatini, Kadek Ayu; Sulindawati, Ni Luh Gede Erni (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
Banking is one of the companies that have the role to support the economy. Conceptually the purpose of the research is to observe financial performance. To find out the health of banks, financial ratios are used through the Risk Based Bank Rating (RBBR) approach and through the performance value tool with the Ecconomic Value Added approach. Thus the results of this study are intended to determine the effect of Non Performing Loan, Loan to Deposit Ratio, Good Coorporate Governance, Net Interest Margin, Return On Asset, Capital Adequacy Ratio and Economic Value Added on the Bank's Stock Price. This type of research is to use quantitative because the use of data is in the form of numbers. Data acquisition is secondary in the financial statements. population use, namely overall listing on the Indonesia Stock Exchange specifically for the period 2014-2018. Sampling by purposive sampling through certain criteria. The number of samples produced was 23 banks in five years. Data processing using multiple linear regression techniques through SPSS version 20. The results showed that partially there were negative influences of Non-Performing Loans, Loan To Deposit Ratio, Good Corporate Governance variables on Stock Prices, while Net Interest Margin, Return On Assets, and Economic Value Added variables had positive effects on Stock Prices. While the Capital Adequacy Ratio has no effect on the Share Price.